ADVERSE REACTIONS TO FIRST-LINE ANTI-TUBERCULOSIS DRUGS AS A RISK FACTOR OF PULMONARY TUBERCULOSIS TREATMENT DEFAULT IN JAKARTA, INDONESIA - SETIAWAN, STEFANUS IMANUEL; ASCOBAT, PURWANTYASTUTI (International Journal of Applied Pharmaceutics, 2019)
Objective: Tuberculosis (TB) is one of the leading fatal infectious diseases and remains a major health problem worldwide. Moreover, adverse effects of TB treatment can escalate treatment default. This study aimed to evaluate the correlation between adverse reactions to anti-TB drugs and treatment default. Methods: We performed a cross-sectional study using medical record data of a total 172 adult patients with pulmonary TB who were treated with first-line anti-TB drugs at Dr. Cipto Mangunkusumo National General Hospital in Jakarta, Indonesia during 2014 and who experienced adverse reactions. Results: Of the total, 127 patients (73.8%) had minor adverse reactions and 45 patients (26.2%) experienced major adverse reactions. Predominant adverse reactions included gastrointestinal disorders (34%) and drug-induced hepatitis (60%). There was a significant correlation between adverse reactions to anti-TB drugs and treatment default cases (odds ratio (OR), 9.33; 95% confidence interval (CI), 4.20–20.72; p<0.001). The results of multivariate analysis showed that TB treatment outcome is affected by adverse drug reactions (OR, 10.91; 95% CI, 4.62–25.75; p<0.001), drug use in treating concomitant diseases (OR, 3.03; 95% CI, 1.30–7.05; p=0.010), and type of anti-TB drug used (OR, 2.41; 95% CI, 0.99–5.83; p=0.045). Conclusion: Based on these results, we showed that adverse reactions to anti-TB drugs can affect TB treatment outcome and can serve as a risk factor to treatment default.